2019
DOI: 10.1155/2019/9731756
|View full text |Cite
|
Sign up to set email alerts
|

Early Marriage, Cohabitation, and Childbearing in West Africa

Abstract: The prevalence of child marriage in West Africa is one of the highest in the global south. Yet, much of what we know about the harmful effects of early marriage and why it persists comes from research on South Asia. Adopting life course family development perspectives on adolescent sexuality, we examine the linkages between the timing of union formation and childbearing across multiple countries with high rates of child marriage. Using the latest round of data from the Demographic and Health Surveys (DHS), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
3
26
1
Order By: Relevance
“…Some studies have shown that opposition from partners [ 56 , 57 ] is the reason why cohabiting women have more unmet need for contraception. Other reasons could be that the desire for childbirth is limited during cohabitation, compared to marriage due to socio-cultural norms surrounding childbirth outside of wedlock in most SSA countries [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that opposition from partners [ 56 , 57 ] is the reason why cohabiting women have more unmet need for contraception. Other reasons could be that the desire for childbirth is limited during cohabitation, compared to marriage due to socio-cultural norms surrounding childbirth outside of wedlock in most SSA countries [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, urban settings may offer better access to contraceptives including condoms, safe abortion and different social norms regarding marriage and fertility. Several studies have shown that adolescents living in urban areas have lower rates of adolescent pregnancy and early marriage, as well as far greater contraceptive use 27–29. Most analyses describe urban–rural differences as a dichotomous stratification, but recent analysis suggests that the urban poor often have equally poor indicators to their rural counterparts 30.…”
Section: Urban–rural Gap Remains Widementioning
confidence: 99%
“…Regarding the latter, Hallfors et al [ 19 ] note that while Zimbabwe’s constitution prohibits child marriages, the enforcement part is lacking. Forced marriage practices have prevailed despite the country being a signatory to the African Charter on the Rights and Welfare of the Child [ 20 ], which places an obligation on member states to end harmful practices such as child marriage, put in place effective actions, including monitoring the progress towards eradicating such practices [ 21 ]. In other words, prohibiting child marriage by law alone has had little effect in eliminating the practice [ 19 , 22 ], perhaps due to “countervailing norms, or widespread exceptions” [ 23 ], some of which are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Child marriage robs young girls of their childhood and is a significant setback for development [ 12 ]. It hinders their full participation in society as well as efforts to achieve gender equality broadly [ 7 , 21 ]. Early marriage also confers risks to sexually transmitted diseases (STIs), including HIV and AIDS, early childbearing and the associated health hazards [ 27 ].…”
Section: Introductionmentioning
confidence: 99%